Translation of Indonesian Cultural Terms in Rainbow Troops Novel: Investigating Translation Procedures - Yesi Yesi; Yudi Juniardi; Akhmad Baihaqi (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2021)
This study is to identify the Indonesian Cultural Terms (ICTs) in Rainbow Troops as the English translated novel by Angie Kilbane from Laskar Pelangi original Indonesian novel by Andrea Hirata and to analyze the translation procedures of ICTs. A qualitative approach is applied in this research by using the content analysis. The result shows that there are five categories of cultural terms such as ecology; material culture; social culture; organizations/customs/ideas/activities/procedures/ concepts, and; gestures and habits. Thev highest percentage of ICT’s is 28.13% which is categorized into organizations, customs, ideas, activities, procedures, concepts. It is a novel with an educational background because it illustrates a lot of activities of teachers and students at school. The translation procedure mostly uses borrowing with 54.17% which proves some vocabulary deficiencies in translated novel since the translator could not find the equivalent cultural terms from the original novel.